Editorial - The Editor (Laureate Education Inc, 2015)
This edition of Higher Learning Research Communications (HLRC) features research from Chile, Spain, and the United States focused on the development of career skills and the different competencies promoted in tertiary education institutions. Since the signing of the Bologna declaration in 1999, a special emphasis has been given to the development of key competencies in higher education in Europe, and around the world. As the research published in this edition portrays, from the adoption of competency-based models in English teaching and assessment to the development of core competencies to promote alumni employability, and even promoting military cultural competency among higher education professionals in institutions that serve military service members and their families, the development of competencies has become an integral part of tertiary education. The issue opens with an invited essay, "Military cultural competency: Understanding how to serve those who serve," by Kimberlee Bethany Bonura and Nicole Lovald, in which the authors propose that higher education professionals should acquire and develop "military cultural competency" in order to better serve the military student population. As Bonura and Lovald explain, this student population in the United States faces unique challenges, from constant moves and deployments to adapting to a civilian life after their service is over, oftentimes with special health concerns after tours of duty in active war zones. There are also challenges regarding knowledge and understanding of the benefits and special federal regulations that apply to service members and their families when they decide to enroll in a university program. It is of particular interest the fact that this student population has a higher rate of enrollment in online programs, given the special mobility circumstances that surround this student population. In terms of the development of student competencies, Oscar García and his colleagues researched whether there are differences in the competency profile of students in terms of gender and age before they graduate. In their article, "Competencies profile of undergraduate students in Madrid's universities: Differences by gender and age," they document there seem to be, in fact, gender differences specific to some competencies, in line with previous research. For instance, the authors found that while women obtain higher scores in organization and teamwork categories, men seem to display higher scores in leadership, adaptation to changes, initiative, problem solving, and decision-making. The authors note these results might be affected by the educational models and evaluations in Europe, which oftentimes give competencies assessments more emphasis, while other research has found women tend to do better in academic assessments. Another area where the development of skills and competencies is crucial is career training. Career development training programs can come from government agencies, corporations and consultants, or colleges and universities. In any case, Anthony and Weide have documented that the type of training program can affect career motivation in project managers and consultants, who are professionals that require complex and varied skills and competencies to succeed professionally. It is of particular interest the fact that, among the subjects interviewed in this study, the ones with technical, business, or graduate degrees saw higher education as more relevant and beneficial than those with generalized degrees. Also related to career development, the emphasis many higher education institutions are placing on English teaching and learning reflects today's globalized world and the need for employment mobility. In his research, Astorga examined how the adoption of a competency-based model in a higher education institute in Chile helped to improve English teaching and assessment. Finally, in "Undergraduate students' perceptions of the communication behaviors of their advisors and perceptions of relational satisfaction," Punyanunt-Carter and Carter explore how the interpersonal communication styles of university advisors affect student satisfaction. In line with previous research, they found assertiveness and responsiveness are important in advisors in order to increase the levels of relational satisfaction with their advisees